Metodologia para construção de produtos de informação nas organizações - Wilson Martins de Assis (2006)
This paper reports the results of a dissertation dealing with research and development to propose a methodology to create information products in organizations, adopting as a benchmark theoretical aspects and the experience of Usiminas Systems Technical InformationDepartment. Concepts developed by renowned authors in the field of information management, like Choo, Davenport, Drucker, McGee, Prusak, Fuld, Richards and others, were reviewed. The proposed methodology takes into consideration the influence of and the need for monitoring theenvironment outside the organization, as well as the importance of information products; the definition of users and the organizations information requirements; information sources; and the dissemination, advertising and use of information products. Information products were split in four categories, namely: reference, news, analytical and statistical. Such categorization enabled to make clear the details for implementing and understanding the various kinds of information product. Moreover, the paper demonstrates that the ultimate purpose of building information products is to serve and support an organizations mission, plans and goals, and to meet the users requirements as well.